2001
DOI: 10.1002/ijc.1377
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of thyroid cancer in a San Francisco Bay area population

Abstract: Using data from a large health plan, we performed a cohort study of thyroid cancer among 204,964 persons (aged 10 -89 at baseline in 1964 -1973, 54% female) followed for a median of 20 years. Thyroid carcinoma is rare, representing 0.5% of cancers among U.S. men and 1.7% cancers among U.S. women, but remains the most common malignancy of the endocrine system. 1 Its incidence increased from 1987 to 1991 in the United States, 2 is greater in women than in men and peaks between the ages of 25 and 65. 3,4 The prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
153
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 44 publications
11
153
4
1
Order By: Relevance
“…Hence, our estimates were not diluted by a possible influence of individuals weight on the disease. Iribarren et al (2001) evaluated several potential predictors of thyroid cancer in a large American cohort with long follow-up, including more than 200 000 persons. Despite the large size of the cohort and the long follow-up, only 196 thyroid cancers were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our estimates were not diluted by a possible influence of individuals weight on the disease. Iribarren et al (2001) evaluated several potential predictors of thyroid cancer in a large American cohort with long follow-up, including more than 200 000 persons. Despite the large size of the cohort and the long follow-up, only 196 thyroid cancers were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Such potential confounding bias associated with socioeconomic status or health consciousness may not be small for papillary adenocarcinoma of the thyroid gland, which is of a highly dormant and silent nature as indicated by a high prevalence rate (6-36 %) of latent papillary carcinoma at autopsy series. 18 Although not all, [19][20][21][22] several previous studies of thyroid cancer have reported a reduced risk of thyroid cancer significantly, [23][24][25][26] or not significantly associated with cigarette smoking. [27][28][29][30][31][32][33] Although results are less consistent, 20,22,24,29,[31][32][33] several studies have also suggested reduced thyroid cancer risk associated with alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between these two factors and thyroid cancer is strange in view of the finding that smokers have increased risk of other thyroid pathologies, such as goiter and nodules, 57,58 which predispose individuals with these conditions to an increased risk of thyroid cancer. In addition to learning more about the hormonal and other biological effects of smoking and drinking, further epidemiologic research is needed to clarify the nature of the inverse association with smoking and drinking, as prospective data available to date 20,22 have failed to confirm this association. Thyroid cancer is relatively infrequent and less fatal than most other malignancies, but presents a significant morbidity burden in the community and warrants more epidemiologic attention than previously given.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have suggested no association with age at menarche, duration of oral contraceptive use, postmenopausal status, ever use of hormone replacement therapy, age at first birth, [18][19][20] smoking, or alcohol consumption, 20 and only 1 out of 3 reported a positive association with parity.…”
mentioning
confidence: 98%